The relationship between isokinetic knee strength and jumping in young male volleyball players - Celenk, B.; Öz, E.; Oner, A. G.; Öz, El. (Turkish Journal of Sport and Exercise, 2019)
Volleyball is a dynamic physical game that does not have a definite match duration but is based on high tempo, quickness, strength, flexibility, endurance and jumping. The aim of this study is to research the relationship between isokinetic knee strength and jumping height in young male volleyball players. 8 male volleyball players aged between 18-22 participated in the research voluntarily. In the study, the physical characteristics of the subjects (body height, body weight, body mass index) were determined, vertical jump heights were measured and at low (600/sec) and high (3000/sec) speeds, the right and left knee flexion/extension concentric isokinetic strength test was applied. Data was analyzed with paired sample t-test and Spearman correlation coefficient test was used to determine the relationship between vertical jump and isokinetic strength (p<0.05).The right and left knees peak torque of the athletes were compared at low and high angular speeds and no significant difference was found. A significant positive correlation was detected between the jumping height and the right knee peak torque at low angular speed (r =.817, p<0.05). This result can be explained by the fact that quadriceps femoris, which is the biggest muscle of the lower extremity, is in the foreground during the jumps that volleyball players perform frequently. It may be advisable to give importance to leg strength training to increase the jump height.